Ciprofloxacin and Metformin as Dual Therapeutic Agents: Synergistic Impact on Cervical Cancer Cell line Proliferation: Insight into Cytoplasmic SRC Tyrosine Kinase Targeting - Jumaa, Azal Hamoody; Hade, Istikrar M.; Abdulla, Kawakeb N; Yasin, Youssef Shakuri (Asian Pacific Journal of Cancer Biology, 2025)
Objective: This study aimed to evaluate the combined effects of ciprofloxacin and metformin on inhibiting cervical cancer proliferation and targeting c-src tyrosine kinase. Methods: The anticancer properties and selective toxicity of a ciprofloxacin-metformin mixture were assessed using HeLa cervical cancer and human fibroblast cell lines (HFF) over 24- and 72-hour incubation periods. Concentrations ranged from 0.1 to 1000 µg/ml, with ciprofloxacin and metformin each at 50% of their concentration in the mixture. A combination index value was calculated to evaluate the synergism between the two drugs, and computational molecular docking simulations were performed to analyze their binding affinity with c-Src tyrosine kinase. Results: The study found that a mixture selectively inhibited cervical cancer cell proliferation based on concentration and treatment duration, with less impact on HFF cell viability compared to cisplatin. A combination index study showed that ciprofloxacin and metformin had a synergistic effect, demonstrating a favorable selectivity for cancer cells over cisplatin. Molecular docking simulations indicated that both ciprofloxacin (-7.9 kcal/mol) and metformin (-5.1 kcal/mol) interacted with c-Src tyrosine kinase at different sites. Conclusion: The study outcomes of the MTT assay, molecular docking, combination index, and selectivity index indicate that the ciprofloxacin-metformin combination presents an effective, safer, and promising option for cervical cancer treatment.